"It's just common sense": Preconceptions and myths regarding fundamental care. (March 2019) - Feo, Rebecca; Frensham, Lauren J.; Conroy, Tiffany; Kitson, Alison
Abstract: Fundamental care has come under increased scrutiny due to high-profile reports globally of poor nursing care. The reasons for these documented care failures are widely debated, with some scholars identifying issues with how fundamental care is valued within healthcare systems and by nurses. During focus groups designed to evaluate a fundamental care education intervention, we identified a perception commonly held by first-year pre-registration (pre-licensure) students that appeared indicative of a de-valuing of fundamental care: students routinely described fundamental care as 'common sense' and doubted that such care should form a key part of their education. In this paper, we explore this perception and its potential consequences for nursing education, clinical practice, and research. We argue that a perception of fundamental care as 'common sense' is a myth; it undermines the inherent complexity of providing such care to a consistently high standard and has negative implications for nursing education and continuing professional development, patient experiences and outcomes, and the advancement of nursing science. It is a perception that must be challenged.